Association between ARID2 and RAS-MAPK pathway in intellectual disability and short stature. Issue 11 (13th October 2020) - Kang, Eungu; Kang, Minji; Ju, Younghee; Lee, Sang-Joon; Lee, Yong-Seok; Woo, Dong-Cheol; Sung, Young Hoon; Baek, In-Jeoung; Shim, Woo Hyun; Son, Woo-Chan; Choi, In Hee; Seo, Eul-Ju; et al.
Abstract : Background: ARID2 belongs to the Switch/sucrose non-fermenting complex, in which the genetic defects have been found in patients with dysmorphism, short stature and intellectual disability (ID). As the phenotypes of patients with ARID2 mutations partially overlap with those of RASopathy, this study evaluated the biochemical association between ARID2 and RAS-MAPK pathway. Methods: The phenotypes of 22 patients with either an ARID2 heterozygous mutation or haploinsufficiency were reviewed. Comprehensive molecular analyses were performed using somatic and induced pluripotent stem cells (iPSCs) of a patient with ARID2 haploinsufficiency as well as using the mouse model of Arid2 haploinsufficiency by CRISPR/Cas9 gene editing. Results: The phenotypic characteristics of ARID2 deficiency include RASopathy, Coffin-Lowy syndrome or Coffin-Siris syndrome or undefined syndromic ID. Transient ARID2 knockout HeLa cells using an shRNA increased ERK1 and ERK2 phosphorylation. Impaired neuronal differentiation with enhanced RAS-MAPK activity was observed in patient-iPSCs. In addition, Arid2 haploinsufficient mice exhibited reduced body size and learning/memory deficit. ARID2 haploinsufficiency was associated with reduced IFITM1 expression, which interacts with caveolin-1 (CAV-1) and inhibits ERK activation. Discussion: ARID2 haploinsufficiency is associated with enhanced RAS-MAPK activity, leading to reduced IFITM1 and CAV-1 expression, thereby increasing ERK activity. This altered interaction might lead to abnormal neuronal development and a short stature.